Peranan Biogas Limbah Ternak Sapi Bantuan PT. Petrochina Bagi Peternak Di Kabupaten Tanjung Jabung Timur Provinsi Jambi - Darmawi, Darlim (Fakultas Peternakan Universitas Jambi, 2009)
The research is aimed to find out how much is the production of biogas from cow dirt, subsidized by PT Petrochina, and it’s role to fulfill veterinarian’s necessity at Tanjung Jabung Timur regency. The research’s method is survey method by using analysis unit of cow veterinarians subsidized by PT Petrochina. The research’s respondents are choosen purposively (Nasir M 1983). The analysis used here is descriptive analysis. The analysis result shows that from 33 people (100% of respondents), the total amount of veterinarian has got cow as much as 65,5 UT and could get cow’s dirt as much as 8952,72 kg / KK / year and resulted biogas in average as much as 1253,39 M 3 /KK/year. While, before veterinarian used biogas, they have spent gasoline and wood as much as 273,72 litre/KK / year and 303,88 bounded of wood / KK/year. In conclusion, biogas has important role as alternative energy for veterinarian to sustitute gasoline and woods, and could ease energy cost so that veterinarian need only 1.177.125 litre gasoline/ KK / year and 1.311.237 bounded of wood / KK / year.